Incidental findings at abdominal ultrasonography in health personnel working with radiation sources - Gündoğdu, Elif; Kebapçı, Mahmut (Journal of Surgery and Medicine, 2018)
Aim: In this study; we aimed to evaluate the incidental lesions detected by ultrasonography in the abdomen and their clinical trials at health personnel working in departments using radiation sources. Methods: Ultrasonography reports on 52 health personnel working in departments using radiation sources were evaluated retrospectively, from the hospital report registry system. The findings were classified as anatomical variant, benign lesions and situations requiring further investigation. Results: In 19 (36.53%) of the workers, the ultrasonography was completely normal. In 33 (63.46%) of the workers, lesions or sonopathological conditions were detected. There were incidental findings in 13 (25%) patients in hepatobilier system, 8 (15.38%) patients in genitourinary system and 12 (23.07%) patients in both of them. 6 (11.53%) workers had a anatomic variant, 24 (46.15%) workers had a benign lesion or condition, and 26 (50%) workers required further examination. Conclusion: Incidental findings are widespread at health personnel working in departments using radiation sources. Some of the findings were benign, while a significant number of cases required further investigation. Knowing commonly detected lesions prevents unnecessary anxiety, while it can ensure that cases requiring further investigation are considered sufficiently.